Effects of the therapy shift from cortisone acetate to modified-release hydrocortisone in a group of patients with adrenal insufficiency - Frigerio, Sofia; Carosi, Giulia; Ferrante, Emanuele; Sala, Elisa; Polledri, Elisa; Fustinoni, Silvia; Ambrosi, Bruno; Chiodini, Iacopo; Mantovani, Giovanna; Morelli, Valentina; Arosio, Maura (Frontiers in Endocrinology, 2023)
Objective Patients with adrenal insufficiency (AI) may be exposed to supraphysiological glucocorticoids levels during standard treatment with cortisone acetate (CA) or immediate-release hydrocortisone (IR-HC). Recent studies, predominantly including patients in IR-HC treatment, suggested that modified-release hydrocortisone (MRH) provide a more physiological cortisol rhythm, improving metabolic control and quality of life. Our primary aim was to assess clinical and biochemical modifications in patients shifted from CA to MRH. Design/Methods We designed a retrospective longitudinal study, enrolling 45 AI patients (22 primary and 23 secondary AI) treated exclusively with CA thrice daily, shifted to MRH once daily; 29/45 patients concluded at least 18-months follow-up (MRH-group). We recruited 35 AI patients continuing CA as a control group (CA-group). Biochemical and clinical data, including metabolic parameters, bone quality, and symptoms of under- or overtreatment were collected. In 24 patients, a daily salivary cortisol curve (SCC) performed before and one month after shifting to MRH was compared to healthy subjects (HS). Results No significant changes in glycometabolic and bone parameters were observed both in MRH and CA-groups during a median follow-up of 35 months. A more frequent decrease in blood pressure values (23.1% vs 2.8%, p=0.04) and improvement of under- or overtreatment symptoms were observed in MRH vs CA-group. The SCC showed a significant steroid overexposure in both CA and MRH-groups compared to HS [AUC (area under the curve) = 74.4 ± 38.1 nmol×hr/L and 94.6 ± 62.5 nmol×hr/L respectively, vs 44.1 ± 8.4 nmol×hr/L, p<0.01 for both comparisons], although SCC profile was more similar to HS in MRH-group. Conclusions In our experience, patients shifted from CA to equivalent doses of MRH do not show significant glycometabolic modifications but blood pressure control and symptoms of over-or undertreatment may improve. The lack of amelioration in glucose metabolism and total cortisol daily exposure could suggest the need for a dose reduction when shifting from CA to MRH, due to their different pharmacokinetics.